Business continuity and disaster recovery planning for it professionals - Snedaker, Susan (Elsevier, 2007)
Increase Your Companys Odds of Surviving a Major Disaster Powerful Earthquake Triggers Tsunami in Pacific. Hurricane Katrina Makes Landfall in the Gulf Coast. Avalanche Buries Highway in Denver. Tornado Touches Down in Georgia These headlines not only have caught the attention of people around the world, they have had a significant effect on IT professionals as well. As technology continues to become more integral to corporate operations at every level of the organization, the job of IT has expanded to become almost all-encompassing. These days, its difficult to find corners of a company that technology does not touch. As a result, the need to plan for potential disruptions to technology services has increased exponentially. Business Continuity Planning (BCP) and Disaster Recovery Planning (DRP) are emerging as the next big thing in corporate IT circles.